Levels of RNA from a family of putative serine protease genes are reduced in Drosophila melanogaster dunce mutants and are regulated by cyclic AMP. - Yun, Y (1989)
We have isolated several genes expressed at abnormal levels in the memory mutant, dunce (dnc), of Drosophila melanogaster. These mutants have an elevated cyclic AMP (cAMP) content due to a mutation in the structural gene for cAMP phosphodiesterase, so the isolated genes are potentially ones regulated by cAMP. Here, we describe the characterization of a genomic clone and corresponding cDNA clones which contain sequences that are underexpressed in dnc mutants. Sequence analysis of portions of the genomic clone and representative cDNAs revealed the presence of two uninterrupted and complete open reading frames (SER1 and SER2) and part of a third (SER3). The predicted amino acid sequences of all of these were found to be homologous to the serine protease family of enzymes. The genomic clone was localized to the polytene chromosome region 99C-D, although genome-blotting experiments indicated the existence of several other genes related to the cloned serine protease-like genes. Hybridization experiments with probes representing each of the three sequenced genes showed that only the SER1-related genes were differentially expressed in dnc mutants. The putative serine protease genes were abundantly expressed in the larval gut, suggesting a major function in digestion. Feeding normal flies cAMP, isobutylmethylxanthine, or forskolin resulted in a decreased RNA level of the SER1-related genes. Thus, RNA levels of this serine protease gene family are negatively regulated by cAMP.